The Protective Effects of Trypsin Inhibitor on Hepatic Ischemia-Reperfusion Injury and Liver Graft Survival. (13th December 2015) - Guan, Lianyue; Liu, Hongyu; Fu, Peiyao; Li, Zhuonan; Li, Peidong; Xie, Lijuan; Xin, Mingang; Wang, Zhanpeng; Li, Wei
Abstract : The aim of this study was to explore the protective effects of ulinastatin (urinary trypsin inhibitor, UTI) on liver ischemia-reperfusion injury (IRI) and graft survival. We employed mouse liver cold IRI and orthotopic liver transplantation (OLTx) models. UTI was added to lactated Ringer's (LR) solution for liver perfusion and preservation in vitro or combined with UTI injection intraperitoneally to the liver graft recipient. Our results indicated that UTI supplementation protected the liver from cold IRI in a dose-dependent manner and prolonged liver graft survival from extended cold preserved liver donors significantly. The underlying mechanism of UTI on liver IRI may be mediated by inhibition of proinflammatory cytokine release, increasing the expression of the antiapoptotic gene Bcl-2 and decreasing the expression of the proapoptosis genes of Caspase-3 and Bax, and further protects hepatocytes from apoptotic death and improves liver function.